2021
DOI: 10.1007/jhep02(2021)036
|View full text |Cite
|
Sign up to set email alerts
|

Black rings in large D membrane paradigm at the first order

Abstract: Black rings are the black objects found in D spacetime dimensional gravity when D ≥ 5. These have event horizon topology SD−3× S1. In this work the solutions of the large D membrane paradigm dual to stationary black rings in Einstein-Maxwell theory with or without cosmological constant are studied. It is shown that the first order membrane equations can only admit static asymptotically flat black rings, and the equilibrium angular velocity for the asymptotically AdS black rings at large D was obtained. The the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…This class of solutions was discovered in [15,16] for D = 5 and then for any D > 4 [17] within 'thin ring' approximation. Later in [1] The asymptotically AdS black rings were found from the first order stationary membrane paradigm, and also the equilibrium rotational speed of the asymptotically flat black ring was determined from the second order equation, which matched with that reported in [2].…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…This class of solutions was discovered in [15,16] for D = 5 and then for any D > 4 [17] within 'thin ring' approximation. Later in [1] The asymptotically AdS black rings were found from the first order stationary membrane paradigm, and also the equilibrium rotational speed of the asymptotically flat black ring was determined from the second order equation, which matched with that reported in [2].…”
Section: Introductionsupporting
confidence: 66%
“…However, [2] also has an asymptotically de Sitter black ring solution which is static at an equilibrium 'ring radius'. This solution was absent from the set of solutions of the stationary membrane paradigm of [1] because the parameters for the reported solution lied outside the domain of validity of [14]. The author indicated that consideration of the second order membrane paradigm should recover this solution, and this note does exactly that.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To recap [1], for stationary axisymmetric configurations the (t, r, θ, s, {χ a }) coordinate system, fondly known as r − s coordinate system, is constructed by splitting the background…”
Section: The Calculationmentioning
confidence: 99%
“…n s s needs to be calculated up to O (ǫ1 )n r = G rr n r + G rs n s = −N g ′ + O ǫ 1 = r − b β + O ǫ 1 , (B.11) n s = G rs n r + G ss n s = N s − ǫ N s L2 (2g − rg ′ ) + O ǫ 2 , (g − (r − b)g ′ ) r n r + ∂ s n s = 2 β + O ǫ 1 , (B.13) Thus from (B.10), (B.12), (B.11) and (B.13), becomes using (B.9) and (B.14), (r − b)g′ − g = β β 2 )(r − b) 2 2 L2 . (B.15)This is a first order ODE which can be easily solved to getg(r) =2β 2 − b) ln(r − b) + C(r − b), (B.16)Where C is the integration constant.…”
mentioning
confidence: 99%